2019
DOI: 10.1017/s0031182019001549
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of Schistosoma haematobium × Schistosoma bovis hybrids in schoolchildren in Côte d'Ivoire

Abstract: Schistosomiasis is a neglected tropical disease, though it is highly prevalent in many parts of sub-Saharan Africa. While Schistosoma haematobium-bovis hybrids have been reported in West Africa, no data about Schistosoma hybrids in humans are available from Côte d'Ivoire. This study aimed to identify and quantify S. haematobium-bovis hybrids among schoolchildren in four localities of Côte d'Ivoire. Urine samples were collected and examined by filtration to detect Schistosoma eggs. Eggs were hatched and 503 mir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 28 publications
0
40
0
Order By: Relevance
“…Further large-scale studies in other regions and countries are now clearly needed, to better understand these risk factors and the generalisability of our findings to sub-Saharan Africa. 17 , 19 , 21 , 24 , 27 , 28 , 41 , 45 Additional work, including modelling studies (to evaluate the role of spillover dynamics in the persistence of Haematobium group hybrids) and experimental infections (to compare the infectiousness of different hybrids in Bulinus spp) could also have a crucial role in evaluating the potential for hybrids to invade and persist in new geographical locations. Incorporating genomic analysis into future work could provide further insights into the origin, mechanisms, and frequency of novel hybridisations—for example, by improving the crucial distinction between S haematobium – S bovis and S haematobium – S curassoni in highly introgressed parasite specimens and optimising identification of F1 hybrids.…”
Section: Discussionmentioning
confidence: 99%
“…Further large-scale studies in other regions and countries are now clearly needed, to better understand these risk factors and the generalisability of our findings to sub-Saharan Africa. 17 , 19 , 21 , 24 , 27 , 28 , 41 , 45 Additional work, including modelling studies (to evaluate the role of spillover dynamics in the persistence of Haematobium group hybrids) and experimental infections (to compare the infectiousness of different hybrids in Bulinus spp) could also have a crucial role in evaluating the potential for hybrids to invade and persist in new geographical locations. Incorporating genomic analysis into future work could provide further insights into the origin, mechanisms, and frequency of novel hybridisations—for example, by improving the crucial distinction between S haematobium – S bovis and S haematobium – S curassoni in highly introgressed parasite specimens and optimising identification of F1 hybrids.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that comparisons of genetic distances from pairs of congeners for both mitochondrial DNA and ITS sequences have demonstrated that mitochondrial DNA sequences of platyhelminths (including schistosomes) accumulate nucleotide substitutions at a much higher rate than ITS [ 28 ]. Moreover, until now, most of the S. haematobium-S. bovis hybrids reported demonstrate the existence of a mitochondrial DNA (i.e., cox 1 and microsatellite DNA) introgressive hybridisation of S. haematobium by S. bovis [ 29 ]. Thus, our developed LAMP assay based on NADH-1 for S. bovis detection would be very useful for detecting S. haematobium-S. bovis hybrids, as most hybrids have a mitochondrial S. bovis signature and a S. haematobium ITS signature.…”
Section: Discussionmentioning
confidence: 99%
“…A rapid diagnostic multiplex PCR was used to target the COI mtDNA gene. We used the technique of Webster et al 2010, optimized by Van den Broeck et al 2011and Angora et al (2019). The primers were one universal reverse primer (Shmb.R: 5′-CAA GTA TCA TGA AAY ART ATR TCT AA-3′) and three species-specific forward primers (for S. haematobium (120 bp) Sh.F: 5′-GGT CTC GTG TAT GAG ATC CTA TAG TTT G-3′, for S. bovis (260 bp) Sb.F: 5′-GTT TAG GTA GTG TAG TTT GGG CTC AC-3′ and for S. mansoni (215 bp) Sm.F: 5′-CTT TGA TTC GTT AAC TGG AGT G-3′).…”
Section: Rapid Diagnostic Multiplex Pcrmentioning
confidence: 99%
“…Africa is also the continent where cases of introgression/hybridization between human and cattle schistosomes are being discovered on a more frequent basis, specifically between S. haematobium and S. bovis. All but one of these cases were found in humans in West Africa: in Niger (introgression of S. haematobium by genes of S. bovis, Brémond et al 1993;Leger et al 2016), in Senegal (bidirectional introgression, Huyse et al 2009;Webster et al 2013), in Mali (hybrids, Soentjens et al 2016, in Côte d'Ivoire (Angora et al 2019), and in Benin (introgressive hybridization, Moné et al 2015). The outlying case was from Corsica (France) (introgressive hybridization, Moné et al 2015).…”
Section: Introductionmentioning
confidence: 99%